Prilagoditev družine na napredovalo maligno bolezen - Potočnik, Darja (Rehabilitacija (Ljubljana), 2013)
Background: An incurable disease is understood as a non-normative event in a persons life; while the process of coping with it and consequential mourning are developmental processes.Confronting an advanced disease requires an adjustment not only of a patient but also of other family members. During the process of disease and mourning the familyis put before different developmental tasks which require various skills and behaviours from the family members. Knowledge of family functioning is therefore required for effective planning of clinical interventions. The treatment of physical, psychological, social and spiritual questions regarding the disease is handled by an interdisciplinary team composed of a doctor, a nurse, a social worker, a psychologist and others. With good understanding of the family dynamics, the medical team can choose appropriate interventions and provide quality care in the time of disease, mourning and rehabilitation. Our study addressed the factors that affect the familys adaptation to the advanced disease and the changes during family dynamics during the course of the disease. Methods: The research took part from October 2010 to July 2011 at the Institute of Oncology in Ljubljana as part of a pilot project of the Ministry of Health of the Republic of Slovenia. Eighty families of patients and their relatives were included; in total, 80 patients and 137 family members participated. For assessing family functioning and qualityof life, we used the Family Assessment Device (FAD),the Family Relationships Index (FRI) and the Functional Assessment of Chronic Illness Therapy Palliative Care Scale (FACIT-Pal). Linear discriminant analysis and multiplelinear regression were used to build multi-variable models. Results: The results showed that cohesion and conflict as dimensions of family functioning have a large effect on quality of life in advanced cancer. Family connectedness, understanding and support, as well as open expression of emotions, especially anger, predict higher quality of life. Conclusions: The results of our research have contributed to understanding structural and process changes in the family during the process of coping with life-threatening disease in a Slovenian sample of patients and their relatives. The research is also of practical value for planning further help/support for the patients and their relatives in order to achieve a holistic and systemic palliative treatment.
Keywords: Adaptation, Psychological; advanced illness; coping; družina; family; family inclusion; kakovost življenja; napredovala bolezen; paliativna oskrba; prilagoditev; Quality of life; rehabilitacija; Rehabilitation; spoprijemanje; standard of living; vključenost družine; vocational rehabilitation